A c.544_618del75bp mutation in the splicing factor gene PRPF31 is involved in non‐syndromic retinitis pigmentosa by reducing the level of mRNA expression. (7th February 2020) - Yang, Dongzhi; Yao, Qihui; Li, Ya; Xu, Yan; Wang, Jun; Zhao, Huiling; Liu, Fuyong; Zhang, Zhaojing; Liu, Yang; Bie, Xiaoshuai; Wang, Yuanli; Xu, Liyan; et al.
Abstract: Purpose: A previous study reported a novel c.544_618del75bp mutation in exon 7 of the PRPF31 gene in a Chinese family with autosomal dominant retinal pigmentosa (ADRP). However, the selected pedigree was a small part of the whole family and the function of the c.544_618del75bp mutation was not explored deeply. The aim of the present study was to validate the previous results and explore the functional significance of the c.544_618del75bp mutation. Methods: We extended the size of the ADRP pedigree and sequenced DNA and cDNA of the PRPF31 gene for all members of the family and 100 healthy controls. Real‐time quantitative polymerase chain reaction (PCR) analysis was performed on the cDNA of patients in the family and cell culture, plasmids transfection and western blot analysis were done to evaluate the functional effect of the mutation in vitro . Results: Sanger sequencing showed that the mutation was present in all patients and absent in all normal individuals, except for participant III‐9. Bioinformatics analysis revealed that the c.544_618del75bp mutation caused a 25 amino acid deletion in the PRPF31 protein. In addition, the mRNA expression assay revealed that the mRNA expression level of the PRPF31 and RP9 genes were significantly lower in RP patients than controls ( p  < 0.05). Finally, the in vitro transfection assay demonstrated that the mRNA expression level of the mutant transfection group was significantly lower than the wild‐type transfection group ( p  < 0.05). Conclusions: Our study suggested that the c.544_618del75bp mutation in the PRPF31 gene was a causative mutation in this ADRP family and affected the expression of RP9 gene by influencing the formation of U4/U6‐U5 tri‐snRNP, eventually leading to the occurrence of RP.